Problems that Affect Quality of Rice Seeds During Processing - SUENA, WAYAN; RAKA, I GUSTI NGURAH; BUDIAWAN, KETUT (Agrotrop : Journal on Agriculture Science; Vol 2 No 1 (2012))
Temporary storage ofthe rice seed during processing, their quality mostly affected by moisture content.Aimed of the experiment is to know the effect of moisture content to the viability of rice seed during processing (short or temporarystorage). The experiment was conducted at Laboratory Department of Agronomy, Faculty of Agriculture, Udayana University. The experiment results show that the interaction effect between moisture content and storage were highly significant to almost all variables observed. The most short dormant occurred at the treatment of 12-14% moisture content for all storage levels. The highest germination capacity obtained at the moisture content of 12-14% with two weeks storage period. The treatment of 21.5% moisture content for all storage levels caused the longest dormancy, with the lowest germination capacity as compared to that of other treatments. Physical tortureaimed to test the storage capacity, where the seeds were treated for 72 hours at 40oC temperature and 100% relative humidity, it was found able to break dormancy.
Keywords: moisture content, storage, rice seed quality, dormancy